If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -2n = n + -4 Reorder the terms: -16 + -2n = -4 + n Solving -16 + -2n = -4 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -16 + -2n + -1n = -4 + n + -1n Combine like terms: -2n + -1n = -3n -16 + -3n = -4 + n + -1n Combine like terms: n + -1n = 0 -16 + -3n = -4 + 0 -16 + -3n = -4 Add '16' to each side of the equation. -16 + 16 + -3n = -4 + 16 Combine like terms: -16 + 16 = 0 0 + -3n = -4 + 16 -3n = -4 + 16 Combine like terms: -4 + 16 = 12 -3n = 12 Divide each side by '-3'. n = -4 Simplifying n = -4
| 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 | | 26-9x=10+7x | | -5x+15=-2x+3 | | 3a+4=6a-2 | | 2x^2+mx+3=x+1 | | f(x)=12+3x | | 12y+11=6y+41 | | 11y-6=93 | | 6(6-6n-3)+3=8n+29 | | 13+3p=7-3p | | 3(x+2)=7(x-2) | | 0.625y-7=-2 | | -5(r+6)=-84 | | 3+5b=3b-1 | | 2[-(x-1)+4]=5+[-(6-7)+9x] | | -7-8r=1-6r-4 | | 8x+7x-66=110-7x | | 3.9=-log(x) | | 4x^2-100=9 |